THE RELATIONSHIP BETWEEN LEADERSHIP STYLE AND JOB SATISFACTION OF NURSES IN HOSPITALS - Dimas Rifqi; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Nurses' job satisfaction is a vital component that influences the quality of hospital services and the sustainability of healthcare delivery. Leadership style, particularly that of head nurses and nurse managers, plays a significant role in shaping nurses' job satisfaction. This study aims to examine the relationship between leadership style and nurses' job satisfaction through a literature review. The method employed was a systematic review of ten national and international articles published between 2015 and 2025 that are relevant to the topic. The findings reveal that transformational, democratic, and participative leadership styles are positively associated with nurses' job satisfaction, as they enhance motivation, loyalty, and create a supportive work climate. In contrast, authoritarian and laissez-faire leadership styles tend to decrease job satisfaction due to limited recognition of nurses' contributions and lack of participatory opportunities. In conclusion, the implementation of effective leadership styles, especially transformational leadership, is essential to improve nurses' job satisfaction and ultimately enhance the overall quality of hospital services.